2017
DOI: 10.1111/his.13235
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological characteristics of interstitial cystitis/bladder pain syndrome without Hunner lesion

Abstract: Non-Hunner-type IC is characterized by severe fibrosis and increased mast cell infiltration, whereas Hunner-type IC is characterized by severe inflammation and urothelial denudation in the entire bladder. Fibrosis in the bladder of IC/BPS patients was correlated with increased urinary frequency and decreased bladder capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 33 publications
(38 reference statements)
3
65
1
Order By: Relevance
“…Secondly, we can consider the fact that recurrence involved a de novo site in 78.2% of cases. Previous histopathological assessment of Hunner‐type IC showed denudation of the urothelium in both HLs and non‐HLs of the bladder mucosa, suggesting the concept of “pancystitis.” Although HLs may represent the most severely damaged part of urothelium, the residual bladder wall (with the gross appearance of normal mucosa) may show microscopic evidence of an inflammatory response. This could possibly explain the current study finding that the baseline PUF bother score and ICI total score were the only independent predictive factors for HLs recurrence and early recurrence, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we can consider the fact that recurrence involved a de novo site in 78.2% of cases. Previous histopathological assessment of Hunner‐type IC showed denudation of the urothelium in both HLs and non‐HLs of the bladder mucosa, suggesting the concept of “pancystitis.” Although HLs may represent the most severely damaged part of urothelium, the residual bladder wall (with the gross appearance of normal mucosa) may show microscopic evidence of an inflammatory response. This could possibly explain the current study finding that the baseline PUF bother score and ICI total score were the only independent predictive factors for HLs recurrence and early recurrence, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, ablation itself did not reduce the recurrence of HLs, and 64.8% of the patients had new HLs at remote sites other than the previous ablation site. Histopathologically, HL type IC has been reported to be characterised by pancystitis . Inflammatory cell infiltration such as an increase in plasma cells, urothelial denudation and expansion of clonal B‐cells was observed in non‐HL from random biopsy as well as in HL.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al. reported that fibrosis and MC counts are increased in IC/BPS without Hunner lesions, suggesting the potential involvement of neurogenic inflammation in its pathophysiology 106 . Elevated gene expression of NGF and transient receptor potential vanilloid type 2 in IC/BPS without Hunner lesions was also reported 23 .…”
Section: Pathophysiology Of Ic/bpsmentioning
confidence: 96%